MENAKAR REPRESENTASI DPRD SEBAGAI PERAN DAKWAH [STUDI KASUS DI DPRD KABUPATEN PONOROGO JAWA TIMUR] - Nur Kholis; Luthfi Ulfa Ni’amah (TASÂMUH, 2017)
This research studied the understanding of legislative members for their function in spreading The religious values of Pancasila at Regional House of Representatives Ponorogo, East Java. By conducting qualitative method, the writer analyzes the implementation of the function and the role of the legislative member as a medium of propaganda, both of chairman of parliament and the members. The data were collected in-depth interview, documentation, and observation. In determining of the data, the writer uses the inspection techniques; credibility, transferability, and dependability for confirming its validity. Then, the data have been analyzed in phases and interconnected between data reduction, data presentation, conclusion, and verification. The study concluded that the legislators understand their function is parallel to their religious values in amar ma’ruf nahi munkar for realizing the values of Pancasila, the aims of democracy, in order to achieve prosperous society, mutual cooperation, mutual respect and managing the diversity of religion, race, and ethnicity in the frame of Bhineka Tunggal Ika.